A Four Quadrature Signals' Generator with Precise Phase Adjustment. (17th May 2016) - Wu, Xiushan; Wang, Yanzhi; An, Siguang; Han, Jianqiang; Sun, Ling
Abstract : A four-way quadrature signals generator with precise phase modulation is presented. It consists of a phase precision regulator and a frequency divider. The phase precision regulator generates two programmable currents by controlling the conduction of the tail current sources and then changes the currents into two bias voltages which are superimposed on the clock signals to adjust the phase difference of the four quadrature signals generated by the frequency divider, making the phase difference of 90 degrees. The four quadrature signals' generator with precise phase modulation has been implemented in a 0.18 μ m mixed-signal and RF 1P6M CMOS technology. The size of the chip including the pads is 675 μ m ⁎ 690 μ m . The circuit uses a supply voltage of 1.8 V, a bias current of 7.2 μ A, and the bits of phase-setting input level n = 6 in the design. The measured results of the four orthogonal signals' phase error can reach ±0.1°, and the phase modulation range can reach ±3.6°.